Association of flower color with pollen reward may explain increased bumblebee visitation to the Scotch broom yellow morph - Devegili, Andrés Matías (2021)
Given that pollinators usually visit flowers for hidden rewards, they need to rely on floral traits that indicate reward status (“honest signals”). However, the relationship between pollination, honest signals, and floral rewards is little documented in natural conditions. The Scotch broom (Cytisus scoparius) is an invasive shrub with polymorphism in the color of its flowers that can be yellow, orange, or red. In three areas dominated by the Scotch broom, we described the abundance of the floral morphs and estimated bumblebee (Bombus terrestris) visitation rate. We examined whether bumblebee visitation to the floral morphs was related to pollen reward. We collected flowers and classified their stamens according to their function: reward or pollen export. Then, we measured anther size and estimated pollen quantity. The yellow morph was more abundant and more visited by bumblebees than the orange and red morphs. The yellow flowers did indeed offer more pollen than the other morphs and this occurred only for rewarding anthers, suggesting that bumblebees could use yellow color as an honest signal to visit the most rewarding flowers. We discuss whether innate and/or learned preferences of bumblebees can explain why the yellow morph is more visited, pollinated, and abundant, while the other morphs are maintained at a lower frequency. This is one of the few field works that shows that variation in intra-specific floral traits is associated with variation in floral reward and pollinator visitation rate, helping to understand the foraging preferences of pollinators and the coexistence of floral morphs in nature. Clinical trials registration: Not applicable.